Postnatal Respiratory Compliance among Premature Ventilated Neonates Associated with Variable Timing and Dosing of Antenatal Steroids - Chawla, Sanjay; Lua, Jorge; Natarajan, Girija; Cortez, Josef Misael C.; Gelmini, Matthew; Thomas, Ronald; Sarnaik, Ashok (American Journal of Perinatology, 2014)
Background Antenatal steroids (ANSs) improve the respiratory compliance of premature infants. Many premature neonates are born before the administration of a complete course of ANS.Objective The objective of this study was to evaluate the respiratory system compliance (Crs) of premature (≤ 32 weeks gestation), intubated neonates in relation to the dose, and timing of ANS administration.Study Design Neonates (n = 61) were divided into four groups based on the dose and timing of ANS exposure: Group 1: no ANS; Group 2: partial course (one dose of betamethasone); Group 3: complete course (two doses of betamethasone administered within 2 weeks of delivery); and Group 4: remote course (two doses of betamethasone administered > 2 weeks before delivery). Crs was measured by single-breath occlusion technique.Results Indexed respiratory compliance ± standard error of the mean (mL/cmH2O/kg) adjusted for gestational ages were 0.359 ± 0.074, 0.366 ± 0.080, 0.625 ± 0.038, and 0.505 ± 0.060 for Groups 1 to 4, respectively. The mean indexed Crs in complete ANS was significantly higher than that of no ANS (0.266 ± 0.085; p = 0.016) as well as partial ANS group (0.259 ± 0.086; p = 0.025).Conclusions Crs after birth was significantly higher among premature intubated neonates born to mothers who received a complete course of ANS within 2 weeks, compared with no ANS or a partial course of ANS.
Keywords: respiratory compliance; antenatal steroids; premature